Key tactics analysis of hospital operation and management by different management levels: A case study in Taiwan. (3rd April 2022) - Lin, Wen-Yu; Lee, Tzong-Ru; Sinnarong, Nirote; Sebastian, Stephanie Gloria; Wang, Ching-Yi
ABSTRACT: This is a study on the critical strategic factors of hospital management. The research was done in one single hospital at central Taiwan with questionnaires distributed to three levels of hospital executives. The senior managers' level includes the board of director, hospital president, and hospital vice superintendent. The mid-level executives' level includes the head of medical department, head of surgical department, head of nursing department, and all chiefs of other departments and divisions. The elementary supervisors' level includes the leaders of technician departments and staffs. This study uses Grey Relational Analysis to analyse the critical strategic factors and to realize the extent of emphasis put on by different levels of executives. The results show that four key strategies of hospital operation are the customer relationship, human resource and talent training, incentive measures and corporate culture, and self-funded medical treatment.